2019
DOI: 10.1098/rsos.190638
|View full text |Cite
|
Sign up to set email alerts
|

Early animal evolution: a morphologist's view

Abstract: Two hypotheses for the early radiation of the metazoans are vividly discussed in recent phylogenomic studies, the ‘Porifera-first’ hypothesis, which places the poriferans as the sister group of all other metazoans, and the ‘Ctenophora-first’ hypothesis, which places the ctenophores as the sister group to all other metazoans. It has been suggested that an analysis of morphological characters (including specific molecules) could throw additional light on the controversy, and this is the aim of this paper. Both h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 96 publications
2
54
0
Order By: Relevance
“…Deep metazoan phylogeny has been a difficult phylogenetic problem, but there are a limited number of plausible arrangements for the major lineages ( Figure 1). The traditional hypothesis (Figure 1a), which is supported by morphology [35] and some phylogenomic analyses [9,11,[36][37][38], places sponges sister to all other metazoans. Many other analyses of large-scale datasets [7,[39][40][41][42] support the hypothesis that ctenophores are sister to all other metazoans ( Figure 1b).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Deep metazoan phylogeny has been a difficult phylogenetic problem, but there are a limited number of plausible arrangements for the major lineages ( Figure 1). The traditional hypothesis (Figure 1a), which is supported by morphology [35] and some phylogenomic analyses [9,11,[36][37][38], places sponges sister to all other metazoans. Many other analyses of large-scale datasets [7,[39][40][41][42] support the hypothesis that ctenophores are sister to all other metazoans ( Figure 1b).…”
Section: Introductionmentioning
confidence: 87%
“…This result is consistent with T2 and T3 but, as we have emphasized elsewhere, T3 is the least plausible of the three possible topologies. After all, T3 fails to explain the distribution of character states highlighted by Nielsen [35] any better than T2 but it has only been recovered in a subset of trees in a few phylogenomic studies [6,42]. Second, we found that the potential for the best-characterized sources of bias in phylogenetics (long-branch attraction and variation in amino acid composition) are likely to have a similar impact on analyses of exposed and buried site data (the relative branch lengths are similar for both structural environments [ Figures 1 and 6c] as are the patterns of variation in amino acid composition [ Figure 6a]).…”
Section: Phylogenetic Implicationsmentioning
confidence: 99%
“…This matrix, although immature, accomplishes an essential function already by regulating diffusion of transforming growth factor β (TGF-β) family ligand Box 1. BM evolution Matrices that contain laminin, nidogen, collagen IV and perlecan together (LNCP matrices) have existed since the Ediacaran period, 600 million years ago, when the first animals originated, and became a stable feature of animal tissues through the Cambrian explosion, which took place 500 million years ago and gave rise to all extant animal phyla (Adams, 2013;Nielsen, 2019;Özbek et al, 2010) (see figure). Laminin-related genes have been found in choanoflagellates, facultative colonial flagellates from which animals evolved (Fahey and Degnan, 2012), and in the even more ancient filasterean amoebas (Sebé-Pedrós et al, 2013).…”
Section: Atypical Bms In the Embryomentioning
confidence: 99%
“…Deep metazoan phylogeny has been a difficult phylogenetic problem, but there are a limited number of plausible arrangements for the major lineages ( Figure 1). The traditional hypothesis (Figure 1a), which is supported by morphology [35] and some phylogenomic analyses (e.g., [9,11,[36][37][38]), places sponges sister to all other metazoans. Other analyses of large-scale datasets (e.g., [7,[39][40][41]) support the hypothesis that ctenophores are sister to all other metazoans ( Figure 1b).…”
Section: Introductionmentioning
confidence: 84%
“…First, we observed that most phylogenetic analyses of exposed and buried sites in the FRG dataset yield distinct topologies (specifically, T2 and T3; e.g., Figure 2). However, of the three plausible topologies, T3 is the least plausible because it fails to explain the distribution of character states highlighted by Nielsen [35] any better than T2 but it has not been recovered in other phylogenomic studies. Second, our analyses revealed that the potential for the best-characterized sources of bias in phylogenetic analyses (long-branch attraction and variation in amino acid composition) to have an impact on phylogenetic analyses of exposed vs. buried sites was quite similar (i.e., the relative branch lengths are similar for both structural environments [ Figure 1 and Figure 6c] and the amount of variation in for variation in amino acid composition is similar for both [ Figure 6a]).…”
Section: Phylogenetic Implicationsmentioning
confidence: 90%